2020
DOI: 10.1111/jvim.15692
|View full text |Cite
|
Sign up to set email alerts
|

Differences in isolation rate and antimicrobial susceptibility of bacteria isolated from foals with sepsis at admission and after ≥48 hours of hospitalization

Abstract: Background Antimicrobial treatment protocols for foals with sepsis that do not improve clinically often are adjusted based on bacteriological and antimicrobial susceptibility testing results from samples collected at hospital admission. Objectives To evaluate whether hospitalization for ≥48 hours affects bacteriological and antimicrobial susceptibility testing results. Animals Two‐hundred sixty‐seven foals <30 days of age admitted to a neonatal intensive care unit and diagnosed with sepsis. Methods Medical rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 31 publications
2
20
0
Order By: Relevance
“…The combination of amikacin and ampicillin has been established to be an appropriate choice of initial treatment of neonatal sepsis in foals in several studies (Theelen et al . 2013, 2019, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The combination of amikacin and ampicillin has been established to be an appropriate choice of initial treatment of neonatal sepsis in foals in several studies (Theelen et al . 2013, 2019, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…These results provide a rationale for repeating bacteriological culture and susceptibility testing of hospitalised foals and emphasise the importance of hospital hygiene in equine neonatal intensive care units (Theelen et al . 2020). It is clear from the studies already published that bacterial susceptibility is also region‐ and hospital‐dependent, therefore local monitoring of this information to guide antimicrobial selection is recommended (Marsh and Palmer 2001a,b; Theelen et al .…”
Section: Part 1: General Considerations For Antimicrobial Selection In Foalsmentioning
confidence: 99%
“…Isolation rates and antimicrobial susceptibility profiles from bacteria isolated from foals with sepsis after > 48h of hospitalisation differ significantly from those collected at hospital admission (Theelen et al . 2020). This demonstrates that previous test results should not be used for selection of alternative drugs for treatment if initial treatment is unsuccessful.…”
Section: Part 2: Specific Antimicrobial Drugs – Indications and Considerationsmentioning
confidence: 99%
“…However, due to increasing microbial resistance, pressure on veterinarians is mounting to adhere to responsible use of antimicrobial drugs. A recent study in a UK referral hospital over a ten-year period demonstrated an increase in prevalence of extended spectrum beta lactamase (ESBL)-producing E. coli as well as increased antimicrobial resistance to frequently used antimicrobials including doxycycline, gentamicin and 3rd generation cephalosporins (Isgren, Edwards et al 2019); other studies have confirmed increasing resistance in bacteria isolated from horses, particularly after antimicrobial therapy (Maddox, Williams et al 2011, Theelen, Wilson et al 2020.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to increasing microbial resistance, pressure on veterinarians is mounting to adhere to responsible use of antimicrobial drugs. A recent study in a UK referral hospital over a 10-year period demonstrated an increase in prevalence of extended-spectrum beta-lactamase (ESBL)producing E. coli as well as increased antimicrobial resistance to frequently used antimicrobials including doxycycline, gentamicin and third-generation cephalosporins (Isgren et al 2019); other studies have confirmed increasing resistance in bacteria isolated from horses, particularly after antimicrobial therapy (Maddox et al 2011;Theelen et al 2020). Unnecessary or unnecessarily long use of antimicrobial drugs enhances development of resistance in pathogens, increases the cost of treatment and exposes the patient to possible side effects, most noticeably disruption of the intestinal microbiome and antimicrobial-induced diarrhoea (Gronvold et al 2010;Johns et al 2012;Barr et al 2013;Costa et al 2015).…”
Section: Introductionmentioning
confidence: 99%